TEACHERS’ COLLABORATION, CREATIVITY AND STUDENTS’ ACADEMIC PERFORMANCE IN SOCIAL STUDIES IN SECONDARY SCHOOLS IN CALABAR EDUCATION ZONE OF CROSS RIVER STATE, NIGERIA - Umaha, Samuel Francis; Essien, Ekenyong Essien (Journal of Continuing and Development Education, 2025)
The purpose of this study was to examine teachers’ collaboration, creativity and students’ academic performance in Social Studies in secondary schools in Calabar Education Zone of Cross River State, Nigeria. To achieve the purpose of this study two null hypotheses were generated to direct the study. Literature review was done according to the variables under study. Correlational research design was adopted for the study. A sample of two hundred and sixty-eight (268) respondents was randomly selected for the study. The selection was done through the stratified random sampling technique. The questionnaire titled “Teachers’ Collaboration, Creativity and Students’ Academic Performance Questionnaire (TCCSAPQ)” and Social Studies performance test was the main instrument used for data collection. The instrument was subjected to face validation by three experts in measurement and evaluation in the Faculty of Education, University of Calabar. The reliability estimate of the instrument was established through the Cronbach alpha reliability method. The reliability coefficient rages from 76 to .85. Regression analysis was the statistical analysis technique adopted to test the hypotheses under study. This statistical tool was used because of the nature of the variables involved in the study. All hypotheses were subjected to testing at .05 level of significance. The results of the analysis revealed that, teachers’ collaboration creativity significantly relate to students’ academic performance. Based on the findings of the study it was recommended among others that teacher Training Programmes should incorporate modules on collaboration and creativity